PEMBINAAN GURU DENGAN SISTEM ANGKA KREDIT - Sugiyono Sugiyono (LPMPP Universitas Negeri Yogyakarta, 2002)
This research was aimed to evaluate the effectiveness of teacher's functional rank advancement by using Credit Number System. The policy of using credit number system in teacher's functional rank advancement is based on a decree ofMen-Pan in 1989 connected with decree No. 84 in 1993. The research was performed by means ofqualitative method. The source of data consists of the teachers, Principals, Evaluating Team, and documentation. Data gathering was triangulation, and data analysis was done by means of inductive methods through the process of data reduction, data display, and verification. Credibility of the data was examined through extended observation, improving persistence, triangulation, peer-check, and member check. The result showed that, first, the system of teacher's rank advancement by using credit number was perceived both positively and negatively. For potential teachers, this system better than pervious automatic rank advancement, but those who were indolent and not quite smart will give negative response, because teacher's wO,rk load will be heavier. Second, this credit grade system has actually not yet effective,as it cannot improve the teacher's motivation, achievementand professionalism; almost all proposals of rank advancement up to level IVla will be granted (without any obstacle) so that it seems like the automatic rank advancement; there was no–